Kajian Hukum Terhadap Tindakan Aborsi Bagi Korban Pemerkosaan Dalam Perspektif Undang-Undang Kesehatan - Elsa Viona Odilia Songgor; I Nyoman Sujana; Kade Richa Mulyawati (Warmadewa Press, 2025)
This article is a normative legal research analyzing abortion. This research focuses on abortion performed by single women after the crime of rape. This is the main focus of the study because there is a conflict of norms between the Criminal Code which strictly prohibits abortion for any reason, and Law No. 17 of 2023 concerning Health which allows it for rape victims and medical emergencies. The author formulates the following problem formulation to overcome these problems. How is the regulation of abortion for rape victims in the Health Act? And what are the implications of abortion for rape victims in the Health Act? The type of research used is normative legal research. Furthermore, the legislative approach is applied in this research. The research shows that in accordance with Law No. 17 of 2023 concerning Health, a lex specialis that provides legal protection to victims of rape against the act of abortion provocatus, abortion against victims of sexual violence is allowed in the applicable area, criminal law as lex generale. However, this is only provided if the victim meets the requirements set out in Government Regulation No. 61/2014 on Reproductive Health.